Molecular cloning and characterization of genistein 4'-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Singh, Somesh; Khan, Bashir Mohammad (Molecular Biology Reports, 2014)
Health related benefits of isoflavones such as genistein are well known. Glycosylation of genistein yields different glycosides like genistein 7-O-glycoside (genistin) and genistein 4'-O-glycoside (sophoricoside). This is the first report on isolation, cloning and functional characterization of a glycosyltransferase specific for genistein 4'-O-glucoside from Bacopa monniera, an important Indian medicinal herb. The glycosyltransferase from B. monniera (UGT74W1) showed 49 % identity at amino acid level with the glycosyltransferases from Lycium barbarum. The UGT74W1 sequence contained all the conserved motifs present in plant glycosyltransferases. UGT74W1 was cloned in pET-30b (+) expression vector and transformed into E. coli. The molecular mass of over expressed protein was found to be around 52 kDa. Functional characterization of the enzyme was performed using different substrates. Product analysis was done using LC-MS and HPLC, which confirmed its specificity for genistein 4'-O-glucoside. Immuno-localization studies of the UGT74W1 showed its localization in the vascular bundle. Spatio-temporal expression studies under normal and stressed conditions were also performed. The control B. monniera plant showed maximum expression of UGT74W1 in leaves followed by roots and stem. Salicylic acid treatment causes almost tenfold increase in UGT74W1 expression in roots, while leaves and stem showed decrease in expression. Since salicylic acid is generated at the time of injury or wound caused by pathogens, this increase in UGT74W1 expression under salicylic acid stress might point towards its role in defense mechanism.
Keywords: Bacopa monniera; Expression analysis; Glycosyltransferase; Immuno-localization; Plant secondary product glycosyltransferase motif